Layered security system on safe using RFID, finger print, camera and keypad based on Internet of Things - Muhammad rehan aulia yazid; Husnaini , Irma (Journal of Industrial Automation and Electrical Engineering, 2025)
The development of technology along with the development of the era touches all aspects of life including the security system. The existence of security systems that are developing with the aim of security can be maintained better, such as in the storage of valuables carried out in safes. Layered security is carried out through four stages, the stages are RFID using a recognized card, fingerprint sensors using fingerprints of people who are allowed to access the safe, facial recognition with ESP32 Cam, and passwords via keypad. The security system must be carried out sequentially and correctly. If an error occurs in passing the security system up to three times, it must be repeated from the beginning again. Using the ESP32 Microcontroller with resources from the power supply, this tool can work well to maintain the security of the safe in layers and will automatically open the safe door so that security can be passed correctly.